Rearing penaeus monodon (Fabricius) post larvae at different densities in wooden boxes with lab-lab - Akeredolu, Betty Chioma (1986)
The possibility of rearing Penaeus monodon larvae from PL5 to PL50 in wooden boxes with lablab was investigated at the Brackishwater Aqquaculture Center, Leganes, Iloilo from November 15, to December 28, 1985. Usng a randomized design, larvae with initial mean weight of 0.9 mg were stocked at 4 densities: 50/m2 (Treatment I), 100/m2 (Treatment II), 150/m2 (Treatment III), and 200/m2 (treatment IV) with 3 replicates in 12 units of 1x1x0.6 m boxes. Lablab was cultured and maintained in the rearing media containing 5-8 % soil organic matter and water salinity of 21-31 ppt. Treatment I gave the highest mea survival (72.70%) an mean net yield (350.14 mg/m2) while the lowest for both variables was obtained in Treatment IV with 49.20% and 217.92 mg/m2 respectively. The regression analysis (P>0.05) showed a significant effect of density on survival and yield of P. monodon (PL5) reared in wooden boxes for 45 days.Physico-chemical and biological parameters fluctuated almost evenly in all the boxes with no significant difference (P>0.05), indicating the effectiveness of the homogenizing technique. Zooplankton correlated positively with survival and yield while ammonia-nitrogen had inverse relationship with yield but negligible correlation with survival. Lablab, however, did ot have correlation with both survival and and yield. The mean survival range of 49.20 -72.70% coupled with the maintenance of predator-free rearing media, good water quality and easy propagation of lablab and zooplankton is an indication of the workability of the system.
Thesis--(M.S. Aquaculture)- College of Fisheries, U.P. in the Visayas, March 1986.
Keywords: Shrimp culture; Feeding and feeds; Algae as feed; Penaeus monodon